2013
DOI: 10.1093/jxb/ers378
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and light regulation of sulphur assimilation and glucosinolate biosynthesis in Arabidopsis

Abstract: Glucosinolates are a major class of sulphur-containing secondary metabolites involved in plant defence against pathogens. Recently many regulatory links between glucosinolate biosynthesis and sulphate assimilation were established. Since sulphate assimilation undergoes diurnal rhythm and is light regulated, this study analysed whether the same is true for glucosinolate biosynthesis. The levels of glucosinolates and glutathione were found to be higher during the day than during the night. This agreed with varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
121
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 54 publications
10
121
2
1
Order By: Relevance
“…However, this mutant had a lower leaf area and root, shoot and whole plant dry weight, as well as a lower accumulation of N, P, K, Ca and Mg in the shoots and whole plant compared with the WT (Table 1 and 2). These results provide evidence that fri has an altered nutritional mechanism based on the interaction between phyA and S. In accordance with this, the transcription factor LONG HYPOCOTYL 5 (HY5), which acts downstream of phyA in Arabidopsis (Ang et al, 1998;Ulm et al, 2004), is involved in the regulation of adenosine 5'-phosphosulphate reductase (APR), a key enzyme for sulfate assimilation (Lee et al, 2011;Huseby et al, 2013). Thus, our results reinforce the idea that phyA plays a role in light signaling in S nutrition, but how this is achieved remains unknown.…”
Section: S Deficiencysupporting
confidence: 69%
“…However, this mutant had a lower leaf area and root, shoot and whole plant dry weight, as well as a lower accumulation of N, P, K, Ca and Mg in the shoots and whole plant compared with the WT (Table 1 and 2). These results provide evidence that fri has an altered nutritional mechanism based on the interaction between phyA and S. In accordance with this, the transcription factor LONG HYPOCOTYL 5 (HY5), which acts downstream of phyA in Arabidopsis (Ang et al, 1998;Ulm et al, 2004), is involved in the regulation of adenosine 5'-phosphosulphate reductase (APR), a key enzyme for sulfate assimilation (Lee et al, 2011;Huseby et al, 2013). Thus, our results reinforce the idea that phyA plays a role in light signaling in S nutrition, but how this is achieved remains unknown.…”
Section: S Deficiencysupporting
confidence: 69%
“…Other authors also found that light can induce the expression of genes involved in GLS biosynthesis [Huseby et al 2013].…”
Section: Resultsmentioning
confidence: 94%
“…This was also observed for the aliphatic glucosinolates, sinigrin and glucoraphanin, at 15/9°C in the present study as well as for some of the indolic and the aromatic glucosinolate. A negative effect of a 24 h light period on glucosinolates may be linked to the lack of circadian rhythm, which is involved in the regulation of glucosinolates in Arabidopsis (Huseby et al, 2013). The effect of day length in our Table 3 Content and composition of fatty acid in kale grown under four different day length and temperature conditions, without and with a subsequent cold acclimatisation period (mg/g dw, 95% confidence interval in brackets study seems to be dependent upon growth temperature, since several of the effects of photoperiod were only found at either high or low growth temperature.…”
Section: Discussionmentioning
confidence: 99%